Effectiveness of Cognitive Behavior Group Therapy in Reducing the Risk of Eating Disorder among University Students - Zaman, Fatema Tu Zohra Binte; Rakib, Shahriar Hasan (Jagannath University Journal of Science, 2024)
Eating disorders are serious mental illnesses that typically originate during adolescence, often persist over an extended period, and significantly affect one's overall well-being. These disorders contribute significantly to the worldwide health burden. Despite a rising number of individuals seeking treatment for eating disorders, there is limited study regarding the effectiveness of therapy in preventive measures of the risk of eating disorders. Therefore, this research aims to study the effectiveness of cognitive behavior group therapy (CBGT) in reducing the risk of eating disorders among university students. Using a pretest-posttest with a control group design. The adapted Bangla version of the Eating Attitude Test (EAT-26) was utilized and socio-demographic data for all participants at the baseline and post-intervention. Thirty-six participants i.e., university students with a risk of eating disorders were chosen by purposive sampling. Participants were randomly assigned into two groups (intervention and non-intervention groups). However, the experimental (intervention) group (n = 18) received cognitive behavioral group therapy, and the control also known as the non-interventional group (n = 18) did not. To analyze the obtained data descriptive statistics, independent sample t-test, and paired sample t-test were performed. Findings showed that receiving CBGT sessions significantly reduced eating disorder risk in the intervention group. However, there is no difference in the risk of eating disorders in the pre-test and post-test of the non-intervention group was observed. This study's findings emphasize the importance and effectiveness of cognitive behavior group therapy in addressing and mitigating the risk of eating disorders among university students. Jagannath University Journal of Science, Volume 10, Number II, Dec. 2023, pp. 124−135